The Impact of the Sustainable Strategy on Strategic Performance: Field Study in the Iraqi Tourism Sector - Alsaad, Muslim Alawi; Lazim, Yusra Yaseen (South Asian Journal of Social Sciences and Humanities, 2023)
The tourism industry, with its two sides (recreational and religious), is one of the important investment fields in Iraq, it is represented Iraq as the second economic source after the oil sector. So a need for serious efforts to develop the tourism sector and maintain its sustainability. This paper will be one of the important contributions in this field; the paper aims to explore the extent of the impact of the sustainable strategy on the level of overall performance in the Iraqi tourism sector. The field of research was some Iraqi tourist institutions at Iraqi tourism, Which covers the field of study on the one side, and can be studied on the other side, for the developing study methodology and organizing its main parts, the research paper adopted a major hypothesis that (there is a statistically significant effect of the sustainable strategy on the level of the overall performance of the Iraqi tourism sector), and for data collection, a checklist was used. The checklist In its questions covers the content required from the study of some tourist institutions in the Iraqi tourism sector, and the list was distributed to a sample of people working in the Iraqi tourism sector, size of the sample (43 people), with experience and academic specialization. The study reached a set of results, the most important of which are: the ability of the sustainable strategy to ensure continuously improve the overall tourism sector performance.